2013
DOI: 10.1371/journal.pone.0055298
|View full text |Cite|
|
Sign up to set email alerts
|

APRIL Induces Tumorigenesis and Metastasis of Colorectal Cancer Cells via Activation of the PI3K/Akt Pathway

Abstract: A proliferation-inducing ligand (APRIL) is highly expressed in colorectal cancer (CRC) tissues and cell lines. However, the biological functions and precise signals elicited by APRIL in CRC have not been fully understood. Here, we used small interfering RNA to selectively deplete APRIL and to determine its tumorigenic effects in a CRC cell line SW480 both in vitro and in vivo. Knockdown of APRIL in SW480 cells was associated with modulation of cell proliferation as well as reduction of cell migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…APRIL was recently reported to activate pAKT to promote colorectal cancer cells proliferation [13], and the phosphorylated AKT could subsequently upregulate the activity of NF-κB [22]. Our results showed that APRIL overexpression in AGS cells significantly increased the phosphorylation of AKT, while silence of APRIL in SGC7901 cells significantly decreased pAKT (Fig.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…APRIL was recently reported to activate pAKT to promote colorectal cancer cells proliferation [13], and the phosphorylated AKT could subsequently upregulate the activity of NF-κB [22]. Our results showed that APRIL overexpression in AGS cells significantly increased the phosphorylation of AKT, while silence of APRIL in SGC7901 cells significantly decreased pAKT (Fig.…”
Section: Resultssupporting
confidence: 59%
“…High levels of APRIL mRNA were expressed in cancers of gastrointestinal tract suggesting a close interrelationship between APRIL and gastrointestinal cancers [3]. Recently, some malignant functions of APRIL have been discovered in colorectal cancer [12,13,32]. Our previous study explored that knockdown of APRIL promoted apoptosis of gastric cancer cells and down-regulated the receptor tyrosine kinases [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus believed to be involved in tumor occurrence, development (35) and metastasis (36). Although activation of PI3K/Akt is more likely associated with increased MMP production and enhanced tumor cell invasion (37,38), it is also true that activation of the PI3k/Akt pathway may be associated with reduced MMP-2 and -9 production, as a result of which the metastatic potency of colon carcinoma cells is decreased (39).…”
Section: Discussionmentioning
confidence: 99%
“…Dendrosome improves the solubility of curcumin and facilitates its uptake by cancer cells, suggesting that this polymer could open new windows to successful drug delivery in cancer therapy (Alizadeh et al, 2012;Babaei et al, 2012). In this study, given the well-known limitations of malignant colorectal cancer treatment strategies, the role of DNC on the cell metastasis and mechanisms involved in this process in SW480 cells-a highly tumorigenic and invasive colon carcinoma cell line (Trainer et al, 1988) with increased expression of genes Zeb 1, Claudin 1, Hef 1 and matrix-metalloproteinases (MMP)-1,-2,-3,-7 and -9 (Nobutomo et al, 2001;Meiko et al, 2002;Hlubek et al, 2004;Murray, 2004;Karadag et al, 2005;Tian et al, 2009;Qin et al, 2010;Amar et al, 2011;Li et al, 2011;Seo and Kim, 2011;Sanchez-Tillo et al, 2013;Wang et al, 2013;Zhao et al, 2013) and hyperactive WNT and Hedgehog signaling pathways (Korinek, 1997;Qualtrough et al, 2004), was evaluated. During carcinoma progression, cancer cells enhance their migratory and invasive capacity through down-regulation of epithelial markers, chiefly the inhibition of E-cadherin and the acquisition of a motile dedifferentiated phenotype as part of the epithelial-to mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%